2017
DOI: 10.1371/journal.pone.0177093
|View full text |Cite
|
Sign up to set email alerts
|

Weekly high-dose liposomal amphotericin B (L-AmB) in critically ill septic patients with multiple Candida colonization: The AmBiDex study

Abstract: BackgroundTo demonstrate the feasibility and safety of weekly high-dose liposomal amphotericin B (L-AmB) (as a pre-emptive antifungal treatment) for 2 weeks in patients with septic shock and Candida colonization.MethodsPilot, multicentre, open-label, prospective study conducted in seven French ICUs. Non-immunocompromised patients, receiving mechanical ventilation were eligible if they presented ICU-acquired severe sepsis requiring newly administered antibacterial agents and Candida colonization in at least two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…after one week of infusion 9,16 . However, prophylaxis or the preemptive use of high L-AmB doses once per week was associated with frequent adverse effects and was not completely safe for fungemia prevention 4,22 . Comparatively, regimens for ambulatory treatment with L-AmB 50 mg or 100 mg four to five times per week yielded median Cmin values of amphotericin B that were higher than the MIC of amphotericin B for the Cryptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…after one week of infusion 9,16 . However, prophylaxis or the preemptive use of high L-AmB doses once per week was associated with frequent adverse effects and was not completely safe for fungemia prevention 4,22 . Comparatively, regimens for ambulatory treatment with L-AmB 50 mg or 100 mg four to five times per week yielded median Cmin values of amphotericin B that were higher than the MIC of amphotericin B for the Cryptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The AmBiDex study evaluated weekly high-dose L-AmB in critically ill septic patients with multiple Candida colonizations [173]. There was no significant increase in serum creatinine levels in patients receiving 10 mg/kg/week L-AmB compared with matched controls [173].…”
Section: Critically Ill Patientsmentioning
confidence: 99%
“…The AmBiDex study evaluated weekly high-dose L-AmB in critically ill septic patients with multiple Candida colonizations [173]. There was no significant increase in serum creatinine levels in patients receiving 10 mg/kg/week L-AmB compared with matched controls [173]. In a phase 3 randomized controlled trial of 537 adult patients receiving at least one dose of micafungin (100 mg/day for patients >40 kg; 2 mg/kg/day for patients ≤40 kg) or L-AmB (3 mg/kg/day), treatment success rates in ICU patients were similar for micafungin (n = 120) vs. L-AmB (n = 110), 62.5% vs. 66.4%, respectively (p = 0.5828) [174].…”
Section: Critically Ill Patientsmentioning
confidence: 99%
“…Data on resistance/ susceptibility would appear to draw a trend of inverse sensitivity between compounds of the echinocandin group and fluconazole, with C. albicans displaying higher figures of resistance to echinocandin compounds than non-albicans species and lower figures of resistance to azole compounds than non-albicans species (Al-Dorzi et al, 2018;Jung et al, 2020;Guner Ozenen et al, 2023). Nevertheless, it has been reported that empirical administration of high-dose liposomal amphotericin B (L-AmB) is associated with better management of fungal invasiveness, less ICU-acquired candidemia, less need for an antifungal agent additional to L-AmB, and ultimately a reduction in ICU mortality, emphasizing the feasibility and relative safety of a preemptive antifungal therapy strategy to combat bloodstream Candida colonization (Azoulay et al, 2017). Regardless of the advancements detailed insofar, this review emphasizes the knowledge gap in molecular factors of resistance for Candida species, particularly when compared to the bacterial agents of sepsis reviewed above.…”
Section: Treatmentmentioning
confidence: 99%